SURFER v3.0: a fast model with ice sheet tipping points and carbon cycle feedbacks for short- and long-term climate scenarios - V. Couplet; M. Martínez Montero; M. Crucifix (Geoscientific Model Development)
Simple climate models that are computationally inexpensive, transparent, and easy to modify are useful for assessing climate policies in the presence of uncertainties. This motivated the creation of SURFER v2.0, a model designed to estimate the impact of CO2 emissions and solar radiation modification on global mean temperatures, sea level rise, and ocean pH. However, SURFER v2.0 is unsuitable for simulations beyond a few thousand years because it lacks some carbon cycle processes. This is problematic for assessing the long-term evolution of the Earth system, particularly the dynamics of ice sheets and the resulting sea level rise. Here, we present SURFER v3.0, an extension to SURFER v2.0 that allows for accurate simulation of the climate, carbon cycle, and sea level rise on timescales ranging from decades to millions of years. We incorporated a dynamic cycling of alkalinity in the ocean, a carbonate sediments reservoir, and weathering fluxes into the model. With these additions, we show that SURFER v3.0 reproduces results from a large class of models, ranging from centennial Coupled Model Intercomparison Project Phase 6 (CMIP6) projections to 1 Myr runs performed with the cGENIE model of intermediate complexity. We show that compared to SURFER v2.0, including long-term carbon cycle processes in SURFER v3.0 leads to a stabilisation of the Greenland ice sheet for the middle of the road emission scenarios and to a significant reduction in the sea level rise contribution from Antarctica for high-emission scenarios.